2000
DOI: 10.1080/07448480009596276
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Vaccination Rates During a Mass Meningococcal Vaccination Program on a College Campus

Abstract: Factors contributing to students' compliance with mass vaccination programs during meningococcal outbreaks have not been well described. A 1997 mass vaccination campaign at Michigan State University provided an opportunity to study such factors. Of 34,024 students in the target population, 17,538 (51.5%) were vaccinated in 5 days. Vaccination rates were higher for women (47.9%) than for men (43.1%) and higher for on-campus residents (65.3%) than for off-campus residents (35.6%). For each year of students' age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…In 1999, 13%, 46%, and 60%, respectively, of incoming Brown University (Providence, RI) freshmen had received MPSV4 (an educational intervention occurred prior to students' arrival in 2000 and 2001) [17]. Other researchers have found that mass immunization campaigns on college campuses following real or perceived meningitis outbreaks have immunized 51% to 87% of the targeted population [18]. In this context, the magnitude of the estimate provided here seems reasonable, recognizing that it is an underestimate.…”
Section: Relationship To Other Studiesmentioning
confidence: 94%
“…In 1999, 13%, 46%, and 60%, respectively, of incoming Brown University (Providence, RI) freshmen had received MPSV4 (an educational intervention occurred prior to students' arrival in 2000 and 2001) [17]. Other researchers have found that mass immunization campaigns on college campuses following real or perceived meningitis outbreaks have immunized 51% to 87% of the targeted population [18]. In this context, the magnitude of the estimate provided here seems reasonable, recognizing that it is an underestimate.…”
Section: Relationship To Other Studiesmentioning
confidence: 94%
“…Coverage increases have been reported after use of school-based vaccination clinics during outbreaks of measles, meningococcal meningitis, and varicella. [22][23][24] However, the role of new adolescent vaccines in controlling outbreaks may be limited, because many of the diseases they prevent have long incubation periods. PARTNERING WITH SCHOOLS However worthy, vaccination may not be a top priority for the administrators and educators who establish school health priorities.…”
Section: Experience With School-based Vaccination In the United Statesmentioning
confidence: 99%
“…The task force's recommendation to vaccinate was not based on the Centers for Disease Control and Prevention (CDC) criteria for an outbreak. The CDC defines a meningococcal outbreak only when there are three cases with group identical strains during a 3-month period [5]. The recommendation arose because multiple cases of confirmed meningococcal disease and other suspected cases had disrupted the functioning of the University to the point where the majority of task force members felt that the intervention was necessary.…”
Section: Recent History Of Infectious Diseases On College Campusesmentioning
confidence: 99%
“…Vaccination was offered for 5 days at one of the gymnasiums on campus; details of this program and characteristics of the students who chose to receive the vaccine have been previously published [5]. In those 5 days, 17,937 students and 1314 staff and dependents were vaccinated.…”
Section: Recent History Of Infectious Diseases On College Campusesmentioning
confidence: 99%